The Heritability of Economic Preferences - Nathan Kettlewell; Agnieszka Tymula; Hong Il Yoo (Institute of Labor Economics (IZA), 2023)
We study the heritability of risk, uncertainty, and time preferences using a field experiment with a large sample of adult twins. We also offer a meta-analysis of existing findings. Our field study introduces a novel empirical approach that marries behavioral genetics with structural econometrics. This allows us to, for the first time, quantify the heritability of economic preference parameters directly without employing proxy measures. Our incentive-compatible experiment is the first twin study to elicit all three types of preferences for the same individual. Compared to previous studies, we find a greater role of genes in explaining risk and uncertainty preferences, and of the shared familial environment in explaining time preferences. Time preferences appear more important from policy and parenting perspectives since they exhibit limited genetic variation and are more than twice as sensitive to the familial environment as risk and uncertainty preferences.
Keywords: C93; D15; D81; D91; Z13; 330; risk preferences; ambiguity aversion; time preferences; twin study; genetics